Expatriate Adjustment Process: The Impact of Accompanying Children on Self-Initiated Expatriates - Zakariyya, Abdul Hameed (2011)
Expatriation as a career choice has been growing and gaining popularity. Even multinational enterprises (MNEs) that once depended entirely on their own staff for postings abroad have begun to recruit from the global self-initiated expatriate (SIE) labour market. Though qualified and competent, SIEs face tremendous challenges in relocation and cross cultural adjustment. Previous research suggests that the greatest challenge both categories of expatriates – businesses backed organizational expatriates (OEs) and self-initiated expatriates (SIEs) ‒ have to face is the adjustment of their spouses and children to the new culture.Reportedly, 80 per cent of expatriates make the transition with spouses and/or children (Shaffer et al., 2001). However, literature is scant on the role of children in expatriation. Children are generally perceived as an encumbrance and hindrance to adjustment abroad Richardson (2004). But, is it really the case? Motivated by the lack of firm and valid answers to the question, this research set out to explore the impact the accompanying children trigger on the adjustment process. It focused on SIE families whose challenges to adjustment are perceived to be greater than those of OE families. SIE families are clearly bereft of any organizational support. Analysis of data from semi-structured interviews with a sample of 9 SIEs suggest that accompanying children on the one hand create additional anxiety and stress while on the other hand they contribute positively through psycho-social and physical support to the adjustment process of SIEs. On the whole, the stresses they create appear to weigh less on the SIEs than the support they render. The findings contradict the popular perception that accompanying children are an encumbrance that must be managed. They suggest that children offer psycho-social and physical support that, indeed, facilitate cross cultural adjustment of SIEs. Furthermore, the findings suggest that children also contribute to family cohesion and the resolution of family conflicts. Older children contribute more to the entire adjustment process than younger children. The findings have useful practical implications for potential SIEs who are held back by fear of coping inabilities as well as for international human resource managers who constantly worry about premature return and the retention of SIEs. Based on the outcomes of this research, potential SIEs need not feel immobile to resort to expatriation simply because of their children who are unfairly regarded as encumbrances. On the organizational side, human resource managers can pay greater heed to recruiting SIEs with older children to reduce early return and increase the chances of retention. More research with access to larger and more diverse samples is required for more reliable results and for better comprehension of the impact of children on adjustment. Such research may focus on the age of children as well as the single or dual career nature of SIE families.